Healthcare Measurement Analysis Using Data mining Techniques (International Journal of Engineering and Computer Science, 2014)
Data mining as one of many constituents of health care has been used intensively and extensively in many organizations around the globe as an efficient technique of finding correlations or patterns among dozens of fields in large relational databases to results into more useful health information. In healthcare, data mining is becoming increasingly popular and essential. Data mining applications can greatly benefits all parties involved in health care industry. The large amount problem generated by healthcare transactions are too complex and voluminous to be processed and analyzed by traditional methods The paper provides a brief review of the existing performance measurement frameworks. On the basis of review, performance measurement system criteria are identified and accordingly a framework has been proposed for measuring performance in healthcare processes. Data mining provides the methodology and technology to transform huge amount of data into useful information for decision making. This paper explores data mining applications in healthcare in it discusses data mining and its applications in major areas such as evaluation of treatment effectiveness, management of healthcare itself and lowering medical costs